Answer:
n = -8
Explanation:
We assume you want to solve the equation
-3(n -5) = 7 -4n
Use the distributive property to eliminate parentheses. Then you have a 3-step linear equation that can be solved in the usual way.
-3n +15 = 7 -4n . . . . . eliminate parentheses
n +15 = 7 . . . . . . . . . . . add 4n to both sides
n = -8 . . . . . . . . . . . . . . subtract 15 from both sides
If the coefficient of n were not 1, then you would divide by that. Here, the "3-step" equation took only 2 steps to solve.
The solution is n = -8.